Hubungan Antara Efektivitas Fungsi Bimbingan dan Konseling Dengan Persepsi Siswa Terhadap Bimbingan dan Konseling di Sekolah Menengah Pertama Stella Duce 1 Yogyakarta - Nuryati, Atamimi (Fakultas Psikologi UGM, 2009)
The aim of this study is to investigate the relationship between the effectiveness of guidance and counselling's function and student's perception towards guidance and counselling in stella duce 1 Middle school of Yogyakarta.